Carbon footprint assessment of microalgal biomass production, hydrothermal liquefaction and refining to sustainable aviation fuel (SAF) in mainland Portugal - Pires, Renata (2024)
ABSTRACT: Industrial liquid effluents (e.g., from fertilizer industry) and flue gas streams (e.g., CO2-rich, from cement industry) arise as an opportunity for waste valorization. Microalgae are suitable biomass for assimilating both effluents at the cultivation stage. Under a biorefinery concept, given the urge for energy transition in the aviation sector, this research explores the transformation of a microalgae consortium grown at an industrial site in Portugal and its subsequent harvesting, hydrothermal liquefaction (HTL), and bio-oil refining. A life cycle assessment (LCA) approach is undertaken with two functional units (FU): 1 kg of microalgae dry-cell weight (dw) and 1 MJ of bio-jet fuel. The latter follows an attributional approach with energy allocation for comparison with the Carbon Offsetting and Reduction Scheme for International Aviation (CORSIA) guidelines. HTL is based on data from bench-scale experiments and literature, whereby the Petroleum Refinery Life Cycle Inventory Model (PRELIM) is used to mimic bio-oil refining. Following this approach, achieving Sustainable Aviation Fuel (SAF) compliance requires net-zero electricity (0 gCO2eq/kWh), with an HTL bio-oil yield of 55.6 % dw (the maximum observed), a minimum refining bio-jet fuel yield of at least 16 %. Alternatively, an HTL bio-oil yield of 36.9 % dw (the median observed) with a refining efficiency of at least 24.3 %.